Flow Injection AAS Determination of Cd, Cu, and Pb at Trace Levels in Wine Using Solid Phase Extraction - Pires Fernandes, Andréa [UNESP]; De Moraes, Mercedes [UNESP]; Gomes Neto, José Anchieta [UNESP] (My University, 2003)
A comparative study is reported between C18 bonded silica gel and powdered polyethylene (PE) as sorbent for Cd, Cu, and Pb determination using ammonium diethyldithiophosphate (ADTP) as the complexing agent in a flow injection system. The complexes were formed in 0.14 mol L-1 HNO 3 and processed in a simple flow system comprising a peristaltic pump, a manual injector-commutator, and a sorbent-packed mini-column. Ethanol was selected as the eluent and analytes in the eluate were determined by flame atomic absorption spectrometry. The optimum concentration of the complexing agent was 0.1% (m/v) ADTP for Cu and Pb determination using either C 18 or PE, and 0.25% (m/v) ADTP for Cd determination using PE. The sample loading flow rates were 5.0, 3.6, and 3.0 mL min-1 for Cu, Pb, and Cd, respectively. The best elution flow rate was 6.5 mL min-1 For a 60-sec preconcentration time, the sampling rate was 40 h-1 and the enrichment factors of 33, 36, and 11 times (C18) or 18, 22, and 23 times (PE) were obtained for Cu, Pb, and Cd, respectively. The limits of detection (LOD) were 1.6 μg L-1 Cu, 11 μg L-1 Pb, and 2.0 μg L-1 Cd using C18 or 2.9 μg L -1 Cu, 19 μg L-1 Pb, and 1.0 μg L-1 Cd using PE, respectively. The relative standard deviations (n = 12) were typically <2%, <2%, and <6% for Cd, Cu, and Pb, respectively. The recoveries of Cd, Cu, and Pb added to wine samples varied from 96-99%, 97-102%, and 90-99%, respectively, using C18 or PE. Accuracy was checked for Cd, Cu, and Pb determination in six wine samples digested by block digestor and open-vessel microwave-assisted digestion systems. The results revealed that C18 was more efficient for Cu and Pb determination, while PE was the best sorbent for Cd.